Pendampingan Pembuatan Merek Usaha, Desain Kemasan Serta Pengurusan IUMK Sebagai Upaya Penguatan Daya Saing Produk Terasi Desa Simpang Lhee Kecamatan Langsa Barat – Kota Langsa - Fuad, Muhammad; Bulan, Tengku Putri Lindung; Chandra, Riny (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
The results of situational analysis were identified the product of shrimp paste produced by the partners of thiscommunity service activity has covered the region of Aceh and Sumatera, some cities in Java Island, and even toMalaysia. Unfortunately their products do not yet have a brand, good packaging design and business legality. Thiscommunity service activity aims to accompany the micro-business of shrimp-processing paste in Simpang Lhee Village inthe making of better brand and packaging design as an effort to strengthen their product competitiveness, and IUMKregistration as proof of the legality of business activity concerned. The implementation of activities begins withconsultation at Geuchik and Director of BUMG Simpang Lhee; then do socialization about the importance of businessbrand and good packaging design on product to the partners of activities;and, accompany partners to fulfill therequirement in handling IUMK business. The main output of this community sevice activity is the existence of businessbrand, better packaging design and IUMK registered number has been obtained as a sign of business legality, as astrengthening of the competitiveness of shrimp paste products belonging to each partner of this activities